2008
DOI: 10.1111/j.1469-1809.2008.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

HMBS Mutations in Chinese Patients with Acute Intermittent Porphyria

Abstract: SummaryAcute intermittent porphyria (AIP), an autosomal dominant disorder, is caused by partial deficiency of hydroxymethylbilane synthase (HMBS) affecting heme biosynthesis. Patients with AIP are characterized by recurrent abdominal pain, port-wine urine, and motor paresis. The disease can be provoked by changes in hormone levels, drugs and fasting. Molecular analysis for twenty-four unrelated Chinese AIP patients from Taiwan identified twenty-five HMBS mutations. There were 10 missense (40%), four nonsense (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Due to the diagnosis of type 1 diabetes, dextrose and insulin were administered at same time. Yang et al have studied the types of HMBS mutations in Chinese patients with AIP and identified twenty-five HMBS mutations [11]. We found HMBS IVS13-2 A>G heterozygous mutation in our patient.…”
Section: Discussionsupporting
confidence: 51%
“…Due to the diagnosis of type 1 diabetes, dextrose and insulin were administered at same time. Yang et al have studied the types of HMBS mutations in Chinese patients with AIP and identified twenty-five HMBS mutations [11]. We found HMBS IVS13-2 A>G heterozygous mutation in our patient.…”
Section: Discussionsupporting
confidence: 51%
“…Identification of disease-specific mutations in the corresponding genes (HMBS, 4 CPOX, and PPOX, respectively) is important for detection and counseling of asymptomatic relatives in families with acute porphyria (1 ). Of the at least 510 mutations that have been identified in these genes (www.hgmd.cf.ac.uk) (3)(4)(5)(6)(7)(8), most are restricted to one or a few families (9,10 ).…”
mentioning
confidence: 99%
“…Therefore, both patients were diagnosed with SIADH. SIADH was noted in approximately 20% of patients with symptomatic AIP in a study of 25 Asians (Yang et al, 2008). This disease can be life-threatening.…”
Section: Discussionmentioning
confidence: 99%
“…Any mutation located in the binding region may disrupt the interaction with the DPM cofactor or disrupt substrate docking during catalysis. Previously reported mutations, such as Q217L, G218R, A219D, G221D, and V222M, caused enzyme abnormalities (Mustajoki et al, 1998;Whatley et al, 1999;Schneider-Yin et al, 2000;Yang et al, 2008). Without additional protein expression measurements, the enzyme activity was assayed from all individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation